ADVERSITY QUOTIENT REMAJA YANG MENGALAMI BROKEN HOME - Dwi Safitri, Zelin Heris; Lasutri Tama, Mulia Marlita (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2019)
Abstract: The purpose of the research is to find out the adversity quotient of adolescents who experienced broken home. What factors influence adversity quotient of adolescents who experience a broken home, and how the description of adversity quotient adolescents who experience a broken home. This study used a qualitative research design and used a case study approach to be able to find out adversity quotient of adolescents who experience broken home. In this study, researchers used 6 sources 2 people as research subjects and 4 people as informants to know from each subject. Rhe results of this study found that adversity quotient adolescents who wxperience broken home have adversity quotient that is not much different. The first subject has four dimentions of adversity quotient, while the second subject only has three of the four dimentions of adversity quotient, each dimention possessed by several factors, namely beliefs, talents, character, passion/willingness, education and environment. Keyword: Adversity Quotient, Adolescence, Broken Home Absrtak: Penelitian ini bertujuan untuk mengetahui adversity quotient remaja yang mengalami broken home. Faktor apa saja yang mempengaruhi adversity quotient remaja yang mengalami broken home, serta bagaimana gambaran adversity quotient remaja yang mengalami broken home. Penelitian ini menggunakan desain penelitian kualitatif serta menggunakan pendekatan studi kasus untuk dapat mengetahui adversity quotient remaja yang mengalami broken home. Dalam penelitian ini, peneliti menggunakan 6 sumber. 2 orang sebagai subjek penelitian dan 4 orang sebagai informan tahu dari masing-masing subjek. Hasil penelitian ini menemukan bahwa adversity quotient remaja yang mengalami broken home memiliki adversity quotient yang tidak jauh berbeda. Subjek pertama memiliki empat dimensi adversity quotient, sementara subjek kedua hanya memiliki tiga dari empat dimensi adversity quotient. Setiap dimensi yang dimiliki oleh subjek juga dipengaruhi oleh beberapa faktor yaitu keyakinan, bakat, karakter, hasrat/kemauan, pendidikan dan lingkungan. Kata Kunci: Adversity Quotient, Remaja, Broken Home